Original articleTrkB deficiency increases survival and regeneration of spinal motoneurons after axotomy in mice - Kotulska, Katarzyna; Larysz-Brysz, Magdalena; Marcol, Wiesław; Malinowska, Izabela; Matuszek, Iwona; Grajkowska, Wiesława; Lewin-Kowalik, Joanna (Folia Neuropathologica, 2006)
Persisting motor function deficit after peripheral nerve injury often results from axotomized motoneuron death. Brain-derived neurotrophic factor (BDNF) and its receptor, trkB, are known to promote peripheral nerve regeneration. However, the requirement of BDNF and trkB for adult motoneuron survival after peripheral nerve injury is not established. We studied the number of surviving and regenerating motoneurons after sciatic nerve transection in wild-type and heterozygous trkB-deficient mice. The nerve was either left cut or immediately sewed up or the gap injury model was performed. The gap was provided with an autologous or cross (obtained from other genetic group) graft. Sixteen weeks after surgery, the animals were sacrificed and histological evaluations were performed. In order to study the number of regenerating motoneurons, immunofluorescent tracer was applied to the distal stump of the operated nerve. We found that in wild type mice, the decrease in motoneurons after nerve transection was markedly higher than in trkB-deficient animals, regardless of the operation procedure. Nerve transection resulted in the highest decrease in motoneuron number in wild type mice. This decrease was lower if the nerve was re-joined using a cross-graft obtained from a trkB-deficient animal. Interestingly, in trkB-deficient animals, the decrease in motoneuron count did not depend on type of operation and was similar after nerve transection, re-joining or grafting. The number of regenerating motoneurons after nerve transection and re-joining in wild type animals was lower than in trkB-deficient mice. The number of regenerating motoneurons after nerve grafting did not differ between groups. These results provide further evidence for the role of trkB receptor in spinal motoneuron survival and regeneration.